Advancing evidence‐based practice through the Knowledge Translation Challenge: Nurses' important roles in research, implementation science and practice change. - Chisholm, Amanda; Russolillo, Angela; Carter, Michelle; Steinberg, Marla; Lambert, Leah; Knox, Andrea; Black, Agnes (Journal of Advanced Nursing (John Wiley & Sons, Inc.), 2025)
Aim: To describe a knowledge translation capacity‐building initiative and illustrate the roles of nurses in practice change using an exemplar case study. Design: The report uses observational methods and reflection. Methods: The Knowledge Translation Challenge program involves a multi‐component intervention across several sites. The advisory committee invited eligible teams to attend capacity‐building workshops. Implementation plans were developed, and successful teams receive funding for a 2 year period. Evaluation involved collecting data on program uptake and impact on practice change. Data has been collected from five cohorts. The exemplar case study employed an action‐research framework. Results: Four nurse‐led teams have demonstrated successful implementation of their practice change. The case study on implementing a clinical toolkit for clozapine management further illustrates a thoughtful planning process, and implementation journey and learnings by a team of nurses. Conclusion: The Knowledge Translation Challenge program empowers nurses to use implementation science practices to enhance the quality and effectiveness of healthcare services. Success of this initiative serves as a model for addressing the persistent gap between knowledge and practice in clinical settings and the value of activating nurses to help close this gap. Implications: As the most trusted and numerous profession, it is vital that nurses contribute to efforts to translate research evidence into clinical practice. The Knowledge Translation Challenge program supports nurses to lead practice change. Impact: The Knowledge Translation Challenge program successfully equips nurses and other health care providers with the knowledge, skills and resources to implement practice improvements which enhance the quality and effectiveness of healthcare services and nursing practice. Patient or Public Contribution: The Knowledge Translation Challenge advisory committee has three patient‐public partners that support teams to develop a patient‐oriented approach for their projects by providing feedback on the implementation plans. Each team was also supported to include patient‐public partners on their project.